Tafsir al Qur'anul karim: pendekatan Syaltut dalam menggali esensi al qur'an - Mahmud Syaltut (C.V. Diponegoro, 1990)
ws/Oen, Jil. 2=c.1-2; jil.3=c.1; jil.4=c.1-4/oen, jil.3=c.2/why, jil. 3=c.3-.4/t, jil.2=c.4-5